Gambaran Faktor-Faktor yang Berhubungan dengan Perilaku Seksual Remaja di SMP Kabupaten Jember - Rizki Fitrianingtyas; Yuni Handayani; Zaida Mauludiyah (ARTERI : Jurnal Ilmu Kesehatan, 2022)
Sexual behavior is a major problem related to various cases of juvenile delinquency. Cases of juvenile delinquency, especially sexual problems that occur from year to year show an increase. This research was conducted with the aim of knowing the description of the factors associated with adolescent sexual behavior. The design of this research is descriptive research. The research variables adolescent knowledge, adolescent attitudes, and adolescent sexual behavior. The research was conducted at SMP N 4 Jember. The research population was all students of SMP N 4 Jember, Jember City with a simple random sampling technique. Research data were collected through observation, questionnaires, and documentation methods. The research data was then processed and analyzed descriptively. The results showed that 40% of students had good knowledge, 55% had sufficient knowledge, 5% lacked knowledge. Sources of information of respondents were 11.7% from magazines/newspapers, 44.1% from television, 17.7% from the internet, from teachers 23.5%. In the attitude calculation results, 100 percent have negative sexual attitudes. A total of 37.7% of respondents had a girlfriend and 100% had held hands, 15% had kissed on the cheek, 5% had kissed on the lips. The better the level of adolescent knowledge, the healthier sexual behavior because the knowledge possessed by adolescents will form a good personality and have an impact on good daily behavior, including adolescent behavior towards premarital sex. Thus increasing knowledge about reproductive health is very important to form good sexual attitudes and behavior.